Pengaruh Media Papan Evaluasi Dalam Pembelajaran Tata Bahasa Arab (Amil Nawasikh) Siswa Kelas VII MTS Al-Amin Bintaro - Lutviana; Suparmanto; Muhammad Muzakkir Hari; Hersa Septi Amelia (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2023)
The problem in this study is the lack of tools or media in evaluating student learning, especially in Arabic language fields or subjects, the lack of an evaluation process in learning. and whether the evaluation board media has an effect learning. This study aims to find out how to improve Arabic grammar skills (amil nawasikh) for grade 7 MTs Al-Amin Bintaro Ampenan by using evaluation board media. It can be concluded that students will easily understand Arabic grammar (amil nawasikh) by using evaluation board media to describe sentence structures, grammar rules, and examples of using grammar visually. Students can see directly how Arabic sentences are formed and understand the relationships between words in sentences. The aims of this study were (1) to identify and describe the inhibiting factors for using evaluation board media to improve Arabic grammar skills in grade 7 MTs Al-Amin Bintaro Ampenan. (2) to find out and describe strategies for using evaluation board media to improve Arabic grammar skills in grade 7 MTs Al-Amin Bintaro Ampenan. In this study, researchers used qualitative methods by using the results of interviews, documentation, and observations from the results of the research which found that students used the media more easily in improving Arabic grammar skills because they could be learned for beginners.